Polyurethane pavement material as well as preparation method and construction process thereof
By using low -cost polyurethane pavement materials and multi -segment compacting processes, the problem of high and slow solidification of polyurethane pavement materials in existing technologies, realized rapid solidification and early strong pavement, and reduced construction costs and time.
Patent Information
- Application Number
- CN202411443936.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing polyurethane pavement materials have problems such as high construction costs, slow curing speed, lack of feasibility of large-scale construction and difficult to guarantee curing effects.
Using low -cost polyurethane pavement materials, including stone combinations, single -component polyurethane adhesives, catalysts, muffins, and low viscosity curing agents. Essence
The low cost, efficient solidification and early strong performance of polyurethane pavement materials have been realized, reducing construction costs, shortening construction time, and improving the density and water seepage effect of the pavement.
Smart Images

Figure BDA0005087161190000031 
Figure BDA0005087161190000032 
Figure BDA0005087161190000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road paving, and in particular to a polyurethane road material and a preparation method and a construction process thereof. Background Art
[0002] Asphalt pavement is the most widely used pavement material, which has the characteristics of good driving comfort, simple construction process and low construction cost. However, asphalt is a temperature-sensitive material, which is seriously affected by temperature changes. It is easy to produce rutting under high temperature conditions in summer and brittle cracking under low temperature conditions in winter. Especially with the frequent occurrence of extreme climates, asphalt pavement materials are increasingly difficult to meet the needs of practical applications. In order to overcome the shortcomings of asphalt pavement materials, researchers have tried to improve the performance of asphalt pavement by adding polymers such as polyethylene, polypropylene, rubber, and polyurethane. However, on the one hand, the process of polymer-modified asphalt is relatively complex and requires high technical personnel and equipment; on the other hand, polymer-modified asphalt needs to solve the problem of compatibility between polymers and asphalt. For this reason, more and more researchers are conducting research on alternatives to asphalt paving materials.
[0003] As a bonding material with excellent performance and low temperature sensitivity, polyurethane adhesives have received more and more attention. Polyurethane adhesives are divided into two types: single-component and two-component. Due to the high requirements of two-component on the site, metering and mixing equipment and construction equipment of the pavement construction site, single-component polyurethane adhesives are mostly used as pavement paving materials at this stage. Single-component polyurethane adhesives are moisture-curing adhesives, which mainly rely on moisture in the air for curing. However, in actual applications, single-component polyurethane mixtures become very dense after paving and rolling (especially dense-graded mixtures). The speed and depth of moisture in the air penetrating into the pavement are greatly slowed down, so the curing speed of the single-component polyurethane pavement becomes abnormally slow or even uncured, which ultimately affects the traffic opening period and road performance of the polyurethane pavement.
[0004] CN116161899A discloses a polyurethane mixture that can promote curing and a preparation method thereof. The polyurethane mixture includes the following components: graded mineral material, polyurethane and composite curing material, and a curing agent exists inside the composite curing material. By using the composite curing material, the curing degree of the polyurethane mixture can be improved, so that the polyurethane mixture can obtain better road performance. The preparation method of the polyurethane mixture is simple and easy, and the raw materials are easy to obtain, which is suitable for mass production. Although this technology provides a curing method for a single-component polyurethane pavement, it has the following shortcomings: first, the composite curing material is a solid and difficult to mix evenly with the polyurethane mixture; second, the absorption amount of the curing agent is difficult to ensure during the preparation of the composite material, and the single-component polyurethane adhesive is a polymer, and its molecules are large and difficult to enter the interior of the porous material; third, the microwave heating equipment is difficult to meet the actual construction requirements of the pavement and the cost is high.
[0005] CN117800649A provides a low-permeability, fast-curing polyurethane mixture for road paving and a preparation method thereof. The polyurethane mixture is prepared by a single-component wet-curing polyurethane adhesive, a limestone material combination, a compound curing agent and a compound catalyst through a certain preparation process. Compared with the existing polyurethane mixture for road paving, while achieving a lower permeability coefficient effect, the traffic opening time is shortened to 24 hours, solving the problem of high permeability coefficient and long traffic opening time of the existing polyurethane pavement. The technology provides a relatively feasible method for rapid curing of polyurethane pavement. However, it has the following shortcomings: on the one hand, the stone used in the polyurethane mixture is the same as the stone used in the existing asphalt pavement, and the construction cost is relatively high; on the other hand, the technology makes clear requirements for the pre-curing conditions of the polyurethane mixture. At the same time, the polyurethane mixture is densely graded, and the curing agent is directly sprayed on the road surface after compaction and molding. The penetration speed and penetration uniformity of the curing agent cannot be guaranteed, and the road curing uniformity is insufficient.
[0006] CN116043646A provides a method for accelerating the curing and forming of a polyurethane pavement and a polyurethane pavement. The method comprises the following steps: obtaining a polyurethane mixture; preheating the screed plate of a paver; using the paver to pave the polyurethane mixture, and using the preheated screed plate to heat it once to obtain a paving surface; rolling the paving surface once to obtain a rolling surface; heating the rolling surface again, and then rolling it a second time to obtain a flat surface; curing the flat surface once, and then spraying it to obtain a polyurethane pavement. The method is simple, reliable, easy to operate, and can achieve the purpose of accelerating the curing and forming of a polyurethane pavement. In addition, the polyurethane pavement of the method has a good curing effect, greatly shortening the curing age of the polyurethane pavement. It is estimated that the curing age can be shortened to 11 to 17 hours, which is about 75% shorter than the existing curing age, and significantly improves the applicability of the polyurethane pavement. However, the disadvantage of this technology is that the paving surface is heated multiple times. When the road surface is thick, the heating efficiency, heating effect and construction efficiency are difficult to guarantee, which is not conducive to the rapid solidification of the road surface. At the same time, for relatively dense road surfaces, the road surface porosity is low after rolling, and the penetration efficiency of the curing agent is reduced during spray treatment, making it difficult to guarantee the road surface solidification speed.
[0007] Therefore, the development of a polyurethane pavement material and construction process that is low-cost, easy to construct, feasible for large-scale construction, and ensures that the pavement is fully solidified is of great significance for the application of polyurethane materials in the paving field. Summary of the invention
[0008] In view of the problems that existing polyurethane road paving materials have high construction costs, slow curing speed, lack of feasibility for large-scale construction and difficulty in ensuring the curing effect, the present invention provides a low-cost, fast-curing, early-strength polyurethane road material and its preparation method and construction process.
[0009] In order to achieve one aspect of the above purpose, the present invention adopts the following technical solution: a polyurethane pavement material, calculated by mass fraction, comprises the following components:
[0010]
[0011] The stone combination is selected from one or more of limestone, basalt, granite and construction solid waste recycling materials, and the curing agent is composed of water and small molecule polyols, the small molecule polyols have a functionality of 3-6, and the small molecule polyols account for 0.01-60% of the total weight of the curing agent.
[0012] In some specific embodiments, the sieve pass rate of the stone combination described in the present invention is as follows:
[0013]
[0014]
[0015] It is easier to obtain a dense polyurethane mixture by setting the above sieve hole pass rate. The sieve hole pass rate of the preferred stone combination is as follows:
[0016]
[0017] In the present invention, limestone, basalt, granite and construction recycling materials are all commonly used stones in the field of highway paving, such as granite, basalt and limestone, and can be crushed stones from stone factories in Yantai and Weihai areas.
[0018] In some specific embodiments, the one-component polyurethane adhesive described in the present invention is obtained by prepolymerizing isocyanate and polyol and then diluting with a solvent, and has an NCO content of 8%-20%, preferably 8.5%-19%, and more preferably 9%-18%.
[0019] In some specific embodiments, the isocyanate described in the present invention is one or more of MDI-100, MDI-50, and PM-200, and the isocyanate is a commercially available product, illustratively including but not limited to: MDI-100, MDI-50, and PM-200 of Wanhua Chemical.
[0020] In some specific embodiments, the functionality of the polyol component is 2-3, and the average molecular weight is preferably 300-6000 g / mol.
[0021] Preferably, the polyol is a commercially available product, illustratively including but not limited to: one or more of C2010D, DL2000, C20240D, C2004, F3156, F3135, F3056D, A303 of Wanhua Chemical (Ningbo) Rongwei Polyurethane Co., Ltd. and castor oil of Guangdong Zhongrun Chemical, further preferably one or more of C2010D, DL2000, F3135, F056D, castor oil, A303, and further preferably one or more of C2010D, DL2000, F3135 castor oil.
[0022] In some specific embodiments, the solvent component is a commercially available product, illustratively including but not limited to: one or more of dioctyl terephthalate from Jiaao Environmental Protection, epoxy soybean oil, dioctyl adipate, dioctyl sebacate, epoxy fatty acid methyl ester, trioctyl trimellitate, and cardanol from Deyi Chemical.
[0023] In some specific embodiments, the curing agent is composed of water and small molecule polyols, the functionality of the small molecule polyols is 3-4, and the small molecule polyols account for 0.01-35% of the total weight of the curing agent. According to the above parameter settings, first, a low-viscosity curing agent can be obtained, simplifying the curing agent addition method; second, the reaction speed of the adhesive and the curing agent can be reduced to provide sufficient operating time for the compaction of the road surface; third, the cross-linking degree of the polyurethane road surface material can be increased, thereby improving the strength of the road surface material.
[0024] Preferably, the small molecule polyol is a commercially available product, illustratively including but not limited to: one or more of trimethylolethane of Keding Chemical, pentaerythritol of Liyang Ruiyang Chemical, glycerol of Shandong Luliyaxin, hexanetriol of Tosoh Chemical, xylitol of Zhejiang Huakang Pharmaceutical, sorbitol of Shouguang Herun Sugar Alcohol, and mannitol of Suzhou Minghua Sugar Alcohol, preferably one or more of trimethylolethane, pentaerythritol, glycerol, hexanetriol, and xylitol, and further preferably one or more of trimethylolethane, glycerol, hexanetriol, and xylitol.
[0025] In some specific embodiments, the viscosity of the curing agent is less than 50 mPa·s, preferably the viscosity of the curing agent is less than 45 mPa·s, and further preferably the viscosity of the curing agent is less than 40 mPa·s; setting the above parameters can ensure that a curing agent with a suitable viscosity is obtained, ensure the atomization effect of the curing agent and reduce the power requirement for the spraying equipment.
[0026] In some specific embodiments, the defoaming agent is a commercially available product, illustratively including but not limited to: one or more selected from BYK011, BYK1760, BYK1794, BYK1795, BYK1799, BYK1790, BYK-A530, BYK-A535 of BYK Chemical, preferably one or more of BYK1760, BYK1794, BYK1795, BYK1790, BYK-A530, BYK-A535, further preferably one or more of BYK1760, BYK1795, BYK1790, BYK-A530, BYK-A535.
[0027] In some specific embodiments, the catalyst described in the present invention is a morpholine catalyst and / or an organometallic catalyst, illustratively including but not limited to: one or more selected from: Y-23, Yutian22, Yutian24 of Liyang Yutian Chemical, JD-32 of Jiangsu Dajiang Chemical, WCAT-WS2, WCAT-WS8, WCAT-WS14, WCAT-WS17 of Yourun, preferably one or more of Y-23, Yutian22, Yutian24, WCAT-WS8, WCAT-WS14, WCAT-WS17, further preferably one or more of Y-23, Yutian24, WCAT-WS8, WCAT-WS14.
[0028] In some specific implementations, the amount of curing agent used for the polyurethane pavement material is determined according to the thickness of the polyurethane pavement, as follows:
[0029] When the thickness of the polyurethane surface layer is 1cm-3cm, the amount of curing agent is 0.3-1.5kg / m 2 , preferably 0.5-1.0kg / m 2 , more preferably 0.6-0.8kg / m 2 ;
[0030] When the thickness of the polyurethane surface layer is 3cm-6cm, the amount of curing agent is 0.5-2.5kg / m 2 , preferably 0.7-2.0kg / m 2 , more preferably 0.8-1.8kg / m 2 ;
[0031] When the thickness of the polyurethane pavement layer is 6-9 cm, the amount of curing agent is 1.2-3.5 kg / m 2 , preferably 1.5-3.0kg / m 2 , more preferably 1.6-2.5kg / m 2 ;
[0032] Another aspect of the present invention provides a method for preparing a polyurethane pavement material, comprising the following steps:
[0033] 1) Dry the stone combination at 100-180℃ to remove water for 7-15h. After the stone is dehydrated, cool it to 10-80℃ for standby use;
[0034] 2) Mixing the cooled stone combination with a single-component polyurethane adhesive, a catalyst, and a defoamer at 10-80° C. and stirring for 30-90 seconds to obtain a polyurethane mixture;
[0035] 3) Keep the polyurethane mixture at a constant temperature of 10-80°C for 2-4 hours. After the constant temperature is completed, place the polyurethane mixture in a rutting plate test mold and evenly spray the curing agent on the surface of the polyurethane mixture;
[0036] 4) Spray the curing agent on the polyurethane pavement material and leave it for a certain period of time before rolling it, as follows:
[0037] When the mixture temperature T ranges from 10<T≤20℃, the mixture sprayed with curing agent is placed at 10-20℃ for 3-5min, compacted 24-48 times, the second compaction is placed at 10-20℃ for 15-20min, compacted 24-48 times, the third compaction is placed at 10-20℃ for 20-35min, compacted 24-48 times, and after compaction, it is placed at room temperature for 6h-72h.
[0038] When the mixture temperature T ranges from 20<T≤30℃, the mixture sprayed with curing agent is placed at 20-30℃ for 3-5min, compacted 24-48 times, the second compaction is placed at 20-30℃ for 15-20min, compacted 24-48 times, the third compaction is placed at 20-30℃ for 10-20min, compacted 24-48 times, and after compaction, it is placed at room temperature for 6h-48h.
[0039] When the mixture temperature T ranges from 30<T≤60℃, the mixture sprayed with curing agent is placed at 30-60℃ for 3-5min, compacted 24-48 times, the second compaction is placed at 30-60℃ for 5-10min, compacted 24-48 times, the third compaction is placed at 30-60℃ for 5-10min, compacted 24-48 times, and after compaction, placed at room temperature for 6h-24h.
[0040] When the mixture temperature T ranges from 60<T<80℃, the mixture evenly sprayed with curing agent is placed at 60-80℃ for 1-3min and then compacted 24-48 times. The second compaction is placed at 60-80℃ for 3-5min and then compacted 24-48 times. The third compaction is placed at 60-80℃ for 3-5min and then compacted 24-48 times. After compaction, it can be placed in room temperature for curing for 6h-16h.
[0041] In some specific embodiments, the preparation method uses a wheel rolling molding machine for compaction operation.
[0042] Another aspect of the present invention provides a construction process for polyurethane pavement materials, comprising the following steps: preparing a polyurethane mixture according to the above method, and
[0043] When the mixture temperature T ranges from 10<T≤20℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, the second compaction is placed under 10-20℃ conditions for 15-20 minutes, and then compacted 1-2 times. The third compaction is placed under 10-20℃ conditions for 20-35 minutes, and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-72h and can be opened to traffic.
[0044] When the mixture temperature T ranges from 20<T≤30℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, the second compaction is placed under 20-30℃ conditions for 15-20 minutes, and then compacted 1-2 times. The third compaction is placed under 20-30℃ conditions for 10-20 minutes, and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-48h and can be opened to traffic.
[0045] When the mixture temperature T ranges from 30<T≤60℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, and compacted for the second time at 30-60℃ for 5-10 minutes and then compacted 1-2 times. The third time is compacted at 30-60℃ for 5-10 minutes and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-24h and can be opened to traffic.
[0046] When the mixture temperature T ranges from 60<T<80℃, the polyurethane pavement that has been paved and evenly sprayed with curing agent is placed under natural conditions for 1-3 minutes and then compacted 1-2 times. The second compaction is placed under 60-80℃ conditions for 3-5 minutes and then compacted 1-2 times. The third compaction is placed under 60-80℃ conditions for 3-5 minutes and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-16h and then opened to traffic.
[0047] In some specific embodiments, the construction process uses rubber-wheel rollers and steel-wheel rollers to perform compaction alternately. For example, the first and third compactions are performed using steel-wheel rollers, and the second compaction is performed using a rubber-wheel roller.
[0048] In the present invention, the polyurethane pavement paving and curing agent spraying are completed simultaneously.
[0049] In some specific implementations, the road surface paving and curing agent simultaneous spraying process is completed by 1 asphalt road surface paver and 1-5 sets of curing agent spraying equipment.
[0050] Compared with the prior art, the present invention has the following advantages:
[0051] (1) The present invention utilizes the strong adhesion of polyurethane adhesive to effectively bond granite stones and construction solid waste recycling materials into high-strength polyurethane road paving materials, thereby solving the problem that asphalt paving materials cannot be used for road paving with granite;
[0052] (2) After the polyurethane mixture is paved, the paved surface is relatively loose. A low-viscosity curing agent far exceeding the theoretical amount (0.04%-0.2%) is evenly sprayed on the surface of the polyurethane mixture. Under the action of gravity, the curing agent infiltrates into the mixture to achieve contact with the mixture. Under the action of rolling, the curing agent is secondary mixed in the mixture to achieve uniform contact with the mixture.
[0053] (3) After the one-component polyurethane mixture is sprayed with the curing agent, the water in the curing agent reacts with the one-component polyurethane adhesive under the action of the low-temperature catalyst to generate gas, release heat and extend the chain. The small molecule polyol in the curing agent and the low-temperature catalyst react quickly to form a cross-linked network. Under the synergistic effect of the two, the curing speed and strength of the polyurethane mixture are improved.
[0054] (4) Under the action of the defoaming agent, the bubbles generated in the polyurethane mixture gradually defoam and diffuse to the road surface, and the generated and accumulated gas is squeezed out through rolling at different time periods. Under the synergistic effect of the two, the gas inside the mixture is eliminated, the density of the polyurethane pavement is improved, and the waterproof effect of the pavement is improved.
[0055] (5) The multi-stage compaction process coordinated with temperature used in the preparation method and construction process of the polyurethane pavement material of the present invention can ensure that the paved polyurethane pavement has time to release the gas generated during the curing process, and ensure that the polyurethane pavement material reaches the required compaction degree.
[0056] The water permeability coefficient of the pavement formed by the polyurethane mixture and process of the present invention can be as low as 11 ml / min, the 8h Marshall stability can be as low as 60 KN, and the 16h Marshall stability can be as low as 80 KN. The technology also has the advantages of low construction cost and low construction operation requirements, and can meet the technical requirements of large-scale construction of polyurethane mixtures.
[0057] Other features and advantages of the present invention will be described in detail through the following detailed description. DETAILED DESCRIPTION
[0058] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are shown in the examples, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.
[0059] In the following specific implementations of the present invention, the materials and equipment involved are as follows:
[0060] (1) Stone combination
[0061] Granite material: Weihai Rushan granite with different particle sizes that conform to the standard of "JTGE42-2005 Highway Engineering Aggregate Test Procedure";
[0062] (2) One-component polyurethane adhesive
[0063] Polyether polyol: C2010: polyoxypropylene polyol, number average molecular weight of 1000, functionality of 2, hydroxyl value of 112.2 mg KOH / g, with propylene glycol as initiator and PO as repeating unit, purchased from Wanhua Rongwei; F3135, number average molecular weight of 4800, functionality of 3, hydroxyl value of 35.1 mg KOH / g; purchased from Wanhua Rongwei;
[0064] Isocyanate: PM-200, MDI-50, and MDI-100 from Wanhua Chemical.
[0065] Solvent: Dioctyl terephthalate, purchased from Zhejiang Jiaao Environmental Protection Co., Ltd.
[0066] (3) Curing agent
[0067] Water: ordinary tap water;
[0068] Small molecule polyols: hexanetriol from Tosoh Chemical;
[0069] Comparative Example 7 Small molecule polyol: ethylene glycol from Yangzi Petrochemical;
[0070] (4) Defoaming agent
[0071] BYK1790 from BYK Chemical;
[0072] (5) Catalyst
[0073] Excellent catalyst WCAT-WS8;
[0074] Comparative Example 8: NiaxA-33 of Momentive;
[0075] (6) Equipment:
[0076] Fully automatic mixing machine, Shanghai Changji, SYD-F02-20;
[0077] Wheel rolling forming machine, Changji, Shanghai, SYD-0703-2;
[0078] Fully automatic mixture pressure tester, Changji, Shanghai, SYD-0730A;
[0079] Water permeability meter, Shandong Luda, HHDS-II.
[0080] The water permeability coefficient shall be implemented in accordance with T 0971 of the "Field Test Procedure for Highway Roadbed and Pavement"; the Marshall stability and splitting strength test methods shall be implemented in accordance with T0709 and T0716 of the "JTG E20-2011 Highway Engineering Asphalt and Asphalt Mixture Test Procedure".
[0081] Example 1
[0082] 1. Preparation of one-component polyurethane adhesive:
[0083] 280.5 g of polyether polyol C2010 and 62.7 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 250.8 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 66 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 1 with an NCO content of 8.0%.
[0084] 2. Preparation of polyurethane rutting plate:
[0085] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 40℃ for standby use;
[0086] 2) The mixing pot was kept at a constant temperature of 40°C in advance, 10230 g of the cooled granite stone combination was placed in the mixing pot, 660 g of polyurethane adhesive, 5.5 g of defoamer BYK1790, and 5.5 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 40°C oven and kept at a constant temperature for 3.5 hours;
[0087] 3) Curing agent preparation: weigh 99.99 g water and 0.01 g hexanetriol (mass fraction 0.01%) in a beaker and stir evenly;
[0088] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 99g of curing agent is evenly spread on the surface of the mixture;
[0089] 5) After the mixture evenly sprayed with curing agent is placed at 40°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 40°C for 10 minutes and then compacted 24 times. The third compaction is placed at 40°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0090] Example 2
[0091] 1. Preparation of one-component polyurethane adhesive:
[0092] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0093] 2. Preparation of polyurethane rutting plate:
[0094] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0095] 2) The mixing pot was kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination was placed in the mixing pot, 275 g of polyurethane adhesive, 11 g of defoamer BYK1790, and 9.9 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0096] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0097] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0098] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0099] Example 3
[0100] 1. Preparation of one-component polyurethane adhesive:
[0101] 83.6 g of polyether polyol C2010 and 125.4 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 167.2 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 41.8 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0102] 2. Preparation of polyurethane rutting plate:
[0103] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 15℃ for standby use;
[0104] 2) The mixing pot was kept at a constant temperature of 15°C in advance, 10450 g of the cooled granite stone combination was placed in the mixing pot, 418 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 15°C oven and kept at a constant temperature for 3.5 hours;
[0105] 3) Curing agent preparation: weigh 105.0 g water and 45.0 g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0106] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 117.15g of curing agent is evenly spread on the surface of the mixture;
[0107] 5) After the mixture evenly sprayed with curing agent is placed at 15°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 15°C for 20 minutes and then compacted 24 times. The third compaction is placed at 15°C for 35 minutes and then compacted 24 times. After the compaction is completed, the fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0108] Example 4
[0109] 1. Preparation of one-component polyurethane adhesive:
[0110] 100.43g of polyether polyol C2010 and 150.645g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80°C, 200.86g of isocyanate PM-200 was added, and the reaction was continued for 2h. The temperature was lowered to 50°C, and 50.215g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0111] 2. Preparation of polyurethane rutting plate:
[0112] 1) Place the stone combination in a blast drying oven and dry it at 120°C to remove water for 8 hours. After the stone is dehydrated, cool it to 65°C for standby use;
[0113] 2) The mixing pot was kept at a constant temperature of 65°C in advance, 10450 g of the cooled granite stone combination was placed in the mixing pot, 502.15 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 35°C oven and kept at a constant temperature for 3.5 hours;
[0114] 3) Curing agent preparation: weigh 70.0 g water and 30.0 g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0115] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 33.0g of curing agent is evenly spread on the surface of the mixture;
[0116] 5) After the mixture evenly sprayed with curing agent is placed at 65°C for 3 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 65°C for 5 minutes and then compacted 24 times. The third compaction is placed at 65°C for 5 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0117] Example 5
[0118] 1. Preparation of one-component polyurethane adhesive:
[0119] 105.6 g of polyether polyol C2010 and 158.4 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 211.2 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 52.8 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0120] 2. Preparation of polyurethane rutting plate:
[0121] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 40℃ for standby use;
[0122] 2) The mixing pot was kept at a constant temperature of 40°C in advance, 10237.15 g of the cooled granite stone combination was placed in the mixing pot, 528.0 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture was placed in a 40°C oven and kept at a constant temperature for 3.5 hours;
[0123] 3) Curing agent preparation: weigh 154g water and 66g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0124] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 220g of curing agent is evenly spread on the surface of the mixture;
[0125] 5) After the mixture evenly sprayed with curing agent is placed at 40°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 40°C for 10 minutes and then compacted 24 times. The third compaction is placed at 40°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0126] Example 6
[0127] 1. Preparation of one-component polyurethane adhesive:
[0128] 105.6 g of polyether polyol C2010 and 158.4 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 211.2 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 52.8 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0129] 2. Preparation of polyurethane rutting plate:
[0130] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 40℃ for standby use;
[0131] 2) The mixing pot was kept at a constant temperature of 40°C in advance, 10340 g of the cooled granite stone combination was placed in the mixing pot, 528.0 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture was placed in a 40°C oven and kept at a constant temperature for 3.5 hours;
[0132] 3) Curing agent preparation: weigh 105g water and 45g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0133] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 117.15g of curing agent is evenly spread on the surface of the mixture;
[0134] 5) After the mixture evenly sprayed with curing agent is placed at 40°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 40°C for 10 minutes and then compacted 24 times. The third compaction is placed at 40°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0135] Comparative Example 1
[0136] 1. Preparation of one-component polyurethane adhesive:
[0137] 100.43g of polyether polyol C2010 and 150.645g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80°C, 200.86g of isocyanate PM-200 was added, and the reaction was continued for 2h. The temperature was lowered to 50°C, and 50.215g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0138] 2. Preparation of polyurethane rutting plate:
[0139] 1) Place the stone combination in a blast drying oven and dry it at 120°C to remove water for 8 hours. After the stone is dehydrated, cool it to 65°C for standby use;
[0140] 2) The mixing pot was kept at a constant temperature of 65°C in advance, 10450 g of the cooled granite stone combination was placed in the mixing pot, 502.15 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 65°C oven and kept at a constant temperature for 3.5 hours;
[0141] 3) Curing agent preparation: weigh 105g water and 45g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0142] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 11.0g of curing agent is evenly spread on the surface of the mixture;
[0143] 5) After the mixture evenly sprayed with curing agent is placed at 65°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 65°C for 10 minutes and then compacted 24 times. The third compaction is placed at 65°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0144] Comparative Example 2
[0145] 1. Preparation of one-component polyurethane adhesive:
[0146] 105.6 g of polyether polyol C2010 and 158.4 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 211.2 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 52.8 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 3 with an NCO content of 10.0%.
[0147] 2. Preparation of polyurethane rutting plate:
[0148] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 40℃ for standby use;
[0149] 2) The mixing pot was kept at a constant temperature of 40°C in advance, 10237.15 g of the cooled granite stone combination was placed in the mixing pot, 528.0 g of polyurethane adhesive, 8.25 g of defoamer BYK1790, and 6.6 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture was placed in a 40°C oven and kept at a constant temperature for 3.5 hours;
[0150] 3) Curing agent preparation: weigh 280.0 g water and 120.0 g hexanetriol (mass fraction 30%) in a beaker and stir evenly;
[0151] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 330g of curing agent is evenly spread on the surface of the mixture;
[0152] 5) After the mixture evenly sprayed with curing agent is placed at 40°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 40°C for 10 minutes and then compacted 24 times. The third compaction is placed at 40°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0153] Comparative Example 3
[0154] 1. Preparation of one-component polyurethane adhesive:
[0155] 280.5 g of polyether polyol C2010 and 62.7 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 250.8 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 66 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 1 with an NCO content of 8.0%.
[0156] 2. Preparation of polyurethane rutting plate:
[0157] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 40℃ for standby use;
[0158] 2) The mixing pot was kept at a constant temperature of 40°C in advance, 10230 g of the cooled granite stone combination was placed in the mixing pot, 660 g of polyurethane adhesive, 5.5 g of defoamer BYK1790, and 3.3 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 40°C oven and kept at a constant temperature for 3.5 hours;
[0159] 3) Curing agent preparation: weigh 99.99 g water and 0.01 g hexanetriol (mass fraction 0.01%) in a beaker and stir evenly;
[0160] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 99g of curing agent is evenly spread on the surface of the mixture;
[0161] 5) After the mixture evenly sprayed with curing agent is placed at 40°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 40°C for 10 minutes and then compacted 24 times. The third compaction is placed at 40°C for 10 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0162] Comparative Example 4
[0163] 1. Preparation of one-component polyurethane adhesive:
[0164] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0165] 2. Preparation of polyurethane rutting plate:
[0166] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0167] 2) The mixing pot was kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination was placed in the mixing pot, 275 g of polyurethane adhesive, 11 g of defoamer BYK1790, and 11.0 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture was placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0168] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0169] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0170] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0171] Comparative Example 5
[0172] 1. Preparation of one-component polyurethane adhesive:
[0173] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0174] 2. Preparation of polyurethane rutting plate:
[0175] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0176] 2) The mixing pot was kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination was placed in the mixing pot, 275 g of polyurethane adhesive, 110 g of defoamer BYK1790, and 9.9 g of catalyst WCAT-WS8 were added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture was placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0177] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0178] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0179] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0180] Comparative Example 6
[0181] 1. Preparation of one-component polyurethane adhesive:
[0182] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0183] 2. Preparation of polyurethane rutting plate:
[0184] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0185] 2) The mixing pot is kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination is placed in the mixing pot, 275 g of polyurethane adhesive and 9.9 g of catalyst WCAT-WS8 are added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture is placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0186] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0187] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0188] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0189] Comparative Example 7
[0190] 1. Preparation of one-component polyurethane adhesive:
[0191] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0192] 2. Preparation of polyurethane rutting plate:
[0193] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0194] 2) The mixing pot is kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination is placed in the mixing pot, 275 g of polyurethane adhesive and 9.9 g of catalyst WCAT-WS8 are added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture is placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0195] 3) Curing agent preparation: weigh 36.0 g water and 64.0 g ethylene glycol (mass fraction 60%) in a beaker and stir evenly;
[0196] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0197] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0198] Comparative Example 8
[0199] 1. Preparation of one-component polyurethane adhesive:
[0200] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0201] 2. Preparation of polyurethane rutting plate:
[0202] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0203] 2) The mixing pot is kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination is placed in the mixing pot, 275 g of polyurethane adhesive and 9.9 g of catalyst NiaxA-33 are added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the polyurethane mixture is placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0204] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0205] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0206] 5) After the mixture evenly sprayed with curing agent is placed at 25°C for 5 minutes, it is compacted 24 times with a wheel roller. The second compaction is placed at 25°C for 20 minutes and then compacted 24 times. The third compaction is placed at 25°C for 20 minutes and then compacted 24 times. After the compaction is completed, a fast-curing early-strength polyurethane pavement material is obtained, and the water permeability coefficient, Marshall stability and splitting strength are tested (the test time is 8h and 16h after rolling molding).
[0207] Comparative Example 9
[0208] 1. Preparation of one-component polyurethane adhesive:
[0209] 30.25 g of polyether polyol C2010 and 30.25 g of polyether polyol F3135 were placed in a three-necked flask, and the three-necked flask was placed in an oil bath and heated. After the temperature rose to 80° C., 187.0 g of isocyanate PM-200 was added, and the reaction was continued for 2 h. The temperature was lowered to 50° C., and 27.5 g of plasticizer dioctyl terephthalate was added to obtain a one-component moisture-curing polyurethane adhesive 2 with an NCO content of 20.0%.
[0210] 2. Preparation of polyurethane rutting plate:
[0211] 1) Place the stone combination in a blast drying oven and dry it at 120℃ to remove water for 8 hours. After the stone is dehydrated, cool it to 25℃ for standby use;
[0212] 2) The mixing pot is kept at a constant temperature of 25°C in advance, 10670 g of the cooled granite stone combination is placed in the mixing pot, 275 g of polyurethane adhesive and 9.9 g of catalyst WCAT-WS8 are added according to the formula ratio and mixed for 90 seconds to obtain the required polyurethane mixture, and the above polyurethane mixture is placed in a 25°C oven and kept at a constant temperature for 3.5 hours;
[0213] 3) Curing agent preparation: weigh 40.0 g water and 60.0 g hexanetriol (mass fraction 60%) in a beaker and stir evenly;
[0214] 4) After the constant temperature is completed, the polyurethane mixture is placed in the rutting plate test mold, and 34.1g of curing agent is evenly spread on the surface of the mixture;
[0215] 5) The mixture evenly sprayed with the curing agent was immediately compacted 24 times by a wheel rolling machine. After the compaction was completed, a conventional polyurethane pavement material was obtained, and the water permeability coefficient, Marshall stability and splitting strength were tested (the test time was 8h and 16h after rolling). The performance data measured by the comparative example and the embodiment are shown in Table 1 below.
[0216] Table 1
[0217]
[0218]
[0219] The difference between Comparative Example 1 and Example 4 is that the amount of curing agent used in Comparative Example 1 is lower than that in Example 4. It can be seen from the data in the table that the Martens stability and splitting strength of Comparative Example 1 at 8h and 16h are significantly lower than those of Example 4, and the water permeability coefficient of Comparative Example 1 is significantly higher than that of Example 4.
[0220] The difference between Comparative Example 2 and Example 5 is that the amount of curing agent used in Comparative Example 2 is higher than that in Example 5. From the data in the table, it can be seen that the Martens stability of Comparative Example 2 at 8h and 16h is lower than that of Example 5. At the same time, the splitting strength of Comparative Example 2 is lower than that of Example 5, that is, the excessive amount of curing agent reduces the bonding strength between the stones.
[0221] The difference between Comparative Example 3 and Example 1 is that the amount of catalyst used in Comparative Example 3 is lower than that in Example 1. From the data in the table, it can be seen that the Martens stability of Comparative Example 3 at 8h and 16h is lower than that of Example 1, that is, the curing speed of Comparative Example 3 is worse than that of Example 1.
[0222] The difference between Comparative Example 4 and Example 2 is that the amount of catalyst used in Comparative Example 4 is higher than that in Example 2. It can be seen from the data in the table that the Martens stability and splitting strength of Comparative Example 4 are lower than those of Example 2, and the water permeability coefficient of Comparative Example 4 is significantly higher than that of Example 2, that is, Comparative Example 4 is more susceptible to water seepage.
[0223] The difference between Comparative Example 5 and Example 2 is that the amount of defoaming agent used in Comparative Example 5 is significantly higher than that in Example 2. It can be seen from the data in the table that the water permeability coefficient of Comparative Example 5 is significantly higher than that of Example 2.
[0224] The difference between Comparative Example 6 and Example 2 is that no defoaming agent is added in Comparative Example 6. It can be seen from the data in the table that the water permeability coefficient of Comparative Example 6 is significantly higher than that of Example 2.
[0225] The difference between Comparative Example 7 and Example 2 is that the curing agent of Comparative Example 7 is obtained by mixing small molecule diol and water, which is obviously different from Example 2. It can be seen from the data in the table that the Martens stability and splitting strength of Comparative Example 7 are significantly lower than those of Example 2, and the water permeability coefficient is significantly higher than that of Example 2.
[0226] The difference between Comparative Example 8 and Example 2 is that the catalyst in Comparative Example 8 is an amine catalyst which is significantly different from Example 2. From the data in the table, it can be seen that the Martens stability and splitting strength of Comparative Example 8 are significantly lower than those of Example 2, and the water permeability coefficient is significantly higher than that of Example 2.
[0227] The difference between Comparative Example 9 and Example 2 is that the compaction process of Comparative Example 9 is obviously different from that of Example 2. It can be seen from the data in the table that the water permeability coefficient of Comparative Example 9 is significantly higher than that of Example 2.
[0228] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the low-cost, fast-curing, early-strength polyurethane pavement material and construction process of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0229] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A polyurethane pavement material, characterized in that: By mass fraction, it includes the following components: The stone combination is selected from one or more of limestone, basalt, granite and construction solid waste recycling materials, and the curing agent is composed of water and small molecule polyols, the small molecule polyols have a functionality of 3-6, and the small molecule polyols account for 0.01-60% of the total weight of the curing agent.
2. The polyurethane pavement material according to claim 1, characterized in that: The sieve aperture pass rates of the stone combination are as follows: when the sieve apertures are 16, 13.2, 9.5, 4.75, 2.36, 1.18, 0.6, 0.3, 0.15, and 0.075 mm, the corresponding pass rates are 100, 90-100, 68-85, 38-68, 24-50, 15-38, 10-2, 7-20, 5-15, and 4-8, respectively; Preferably, the sieve hole pass rate of the stone combination is as follows: when the sieve holes are 16, 13.2, 9.5, 4.75, 2.36, 1.18, 0.6, 0.3, 0.15, and 0.075 mm, respectively, the corresponding pass rates are 100, 96-100, 70-83, 38-50, 25-40, 18-30, 13-20, 7-17, 5-13, and 4-8.
3. The polyurethane pavement material according to claim 1, characterized in that: The one-component polyurethane adhesive is obtained by prepolymerizing isocyanate and polyol and then diluting with a solvent, and has an NCO content of 8%-20%, preferably 8.5%-19%, and more preferably 9%-18%.
4. The polyurethane pavement material according to claim 3, characterized in that: The isocyanate is one or more of MDI-100, MDI-50, and PM-200; and / or, The polyol has a functionality of 2-3 and an average molecular weight of preferably 300-6000 g / mol; and / or, The polyols include, but are not limited to: one or more of C2010D, DL2000, C20240D, C2004, F3156, F3135, F3056D, A303 of Wanhua Chemical Rongwei Polyurethane Co., Ltd. and castor oil of Guangdong Zhongrun Chemical, more preferably one or more of C2010D, DL2000, F3135, F056D, castor oil, A303, and more preferably one or more of C2010D, DL2000, F3135 castor oil; and / or, The solvent includes but is not limited to: one or more of dioctyl terephthalate from Jiaao Environmental Protection, epoxy soybean oil, dioctyl adipate, dioctyl sebacate, epoxy fatty acid methyl ester, trioctyl trimellitate, and cardanol from Deyi Chemical.
5. The polyurethane pavement material according to claim 1, characterized in that: In the curing agent, the functionality of the small molecule polyol is 3-4, and the small molecule polyol accounts for 0.01-35% of the total weight of the curing agent; and / or, The viscosity of the curing agent is less than 50 mPa·s, preferably the viscosity of the curing agent is less than 45 mPa·s, and more preferably the viscosity of the curing agent is less than 40 mPa·s; Preferably, the small molecule polyol includes, but is not limited to, one or more of trimethylolethane of Keding Chemical, pentaerythritol of Liyang Ruiyang Chemical, glycerol of Shandong Luliyaxin, hexanetriol of Tosoh Chemical, xylitol of Zhejiang Huakang Pharmaceutical, sorbitol of Shouguang Herun Sugar Alcohol, and mannitol of Suzhou Minghua Sugar Alcohol, preferably one or more of trimethylolethane, pentaerythritol, glycerol, hexanetriol, and xylitol, and further preferably one or more of trimethylolethane, glycerol, hexanetriol, and xylitol.
6. The polyurethane pavement material according to any one of claims 1 to 5, characterized in that: The defoaming agent includes, but is not limited to, one or more selected from BYK011, BYK1760, BYK1794, BYK1795, BYK1799, BYK1790, BYK-A530, and BYK-A535 of BYK Chemical, preferably one or more of BYK1760, BYK1794, BYK1795, BYK1790, BYK-A530, and BYK-A535, and further preferably one or more of BYK1760, BYK1795, BYK1790, BYK-A530, and BYK-A535.
7. The polyurethane pavement material according to any one of claims 1 to 6, characterized in that: The moisture curing catalyst is a morpholine catalyst and / or an organic metal catalyst, including but not limited to: one or more selected from Y-23, Yutian22, Yutian24 of Liyang Yutian Chemical, JD-32 of Jiangsu Dajiang Chemical, WCAT-WS2, WCAT-WS8, WCAT-WS14, and WCAT-WS17 of Yourun, preferably one or more of Y-23, Yutian22, Yutian24, WCAT-WS8, WCAT-WS14, and WCAT-WS17, and further preferably one or more of Y-23, Yutian24, WCAT-WS8, and WCAT-WS14.
8. The polyurethane pavement material according to any one of claims 1 to 7, characterized in that: The amount of curing agent used for the polyurethane pavement material is determined according to the thickness of the polyurethane pavement, as follows: When the thickness of the polyurethane surface layer is 1cm-3cm, the amount of curing agent is 0.3-1.5kg / m 2 , preferably 0.5-1.0kg / m 2 , more preferably 0.6-0.8kg / m 2 ; When the thickness of the polyurethane surface layer is 3cm-6cm, the amount of curing agent is 0.5-2.5kg / m 2 , preferably 0.7-2.0kg / m 2 , more preferably 0.8-1.8kg / m 2 ; When the thickness of the polyurethane pavement layer is 6cm-9cm, the amount of curing agent is 1.2-3.5kg / m 2 , preferably 1.5-3.0kg / m 2 , more preferably 1.6-2.5kg / m 2 .
9. The method for preparing the polyurethane pavement material according to any one of claims 1 to 8, characterized in that: The steps include: 1) Dry the stone combination at 100-180℃ to remove water for 7-15h. After the stone is dehydrated, cool it to 10-80℃ for standby use; 2) Mixing the cooled stone combination with a single-component polyurethane adhesive, a catalyst, and a defoamer at 10-80° C. and stirring for 30-90 seconds to obtain a polyurethane mixture; 3) Keep the polyurethane mixture at a constant temperature of 10-80°C for 2-4 hours. After the constant temperature is completed, place the polyurethane mixture in a rutting plate test mold and evenly spray the curing agent on the surface of the polyurethane mixture; 4) Spray the curing agent on the polyurethane pavement material and leave it for a certain period of time before rolling it, including: When the mixture temperature T ranges from 10<T≤20℃, the mixture sprayed with curing agent is placed at 10-20℃ for 3-5min, compacted 24-48 times, the second compaction is placed at 10-20℃ for 15-20min, compacted 24-48 times, the third compaction is placed at 10-20℃ for 20-35min, compacted 24-48 times, and after compaction, placed in room temperature for curing for 6h-72h; When the mixture temperature T ranges from 20<T≤30℃, the mixture sprayed with curing agent is placed at 20-30℃ for 3-5min, compacted 24-48 times, the second compaction is placed at 20-30℃ for 15-20min, compacted 24-48 times, the third compaction is placed at 20-30℃ for 10-20min, compacted 24-48 times, and after compaction, placed in room temperature for 6h-48h. When the mixture temperature T ranges from 30<T≤60℃, the mixture sprayed with curing agent is placed at 30-60℃ for 3-5min, compacted for 24-48 times, the second compaction is placed at 30-60℃ for 5-10min, compacted for 24-48 times, the third compaction is placed at 30-60℃ for 5-10min, compacted for 24-48 times, and after compaction, placed at room temperature for 6h-24h; When the mixture temperature T ranges from 60<T<80℃, the mixture evenly sprayed with curing agent is placed at 60-80℃ for 1-3min and then compacted 24-48 times. The second compaction is placed at 60-80℃ for 3-5min and then compacted 24-48 times. The third compaction is placed at 60-80℃ for 3-5min and then compacted 24-48 times. After compaction, it is placed at room temperature for curing for 6h-16h.
10. The construction process of the polyurethane pavement material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: preparing a polyurethane mixture according to the method of claim 9, and When the mixture temperature T ranges from 10<T≤20℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, the second compaction is placed under 10-20℃ conditions for 15-20 minutes, and then compacted 1-2 times. The third compaction is placed under 10-20℃ conditions for 20-35 minutes, and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-72h and can be opened to traffic. When the mixture temperature T ranges from 20<T≤30℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, the second compaction is placed under 20-30℃ conditions for 15-20 minutes, and then compacted 1-2 times. The third compaction is placed under 20-30℃ conditions for 10-20 minutes, and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-48h and can be opened to traffic. When the mixture temperature T ranges from 30<T≤60℃, the polyurethane pavement that has been paved and sprayed with curing agent evenly is placed under natural conditions for 3-5 minutes, compacted 1-2 times, and compacted for the second time at 30-60℃ for 5-10 minutes and then compacted 1-2 times. The third time is compacted at 30-60℃ for 5-10 minutes and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-24h and can be opened to traffic. When the mixture temperature T ranges from 60<T<80℃, the polyurethane pavement that has been paved and evenly sprayed with curing agent is placed under natural conditions for 1-3 minutes and then compacted 1-2 times. The second compaction is placed under 60-80℃ conditions for 3-5 minutes and then compacted 1-2 times. The third compaction is placed under 60-80℃ conditions for 3-5 minutes and then compacted 1-2 times. After compaction, it is cured under natural conditions for 6h-16h and then opened to traffic.
Citation Information
Patent Citations
Low-water-seepage fast-curing polyurethane mixture and preparation method thereof
CN117800649A